1979
DOI: 10.1111/j.1460-2695.1979.tb01083.x
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Prior Austenite Grains in Fatigue Crack Initiation and Propagation in Low Carbon Martensite

Abstract: Abstract-A study has been made of the role of Prior Austenite Grains (PAG) in fatigue crack initiation and propagation in low carbon martensite.The occiirrence of ferrite precipitation along prior austenite grain boundaries during rapid cooling will lead to the formation of intergranular cracking. This intergranular cracking has a close relationship with the reduction of the endurance limit for fine grained low carbon martensite.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1981
1981
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…However, with increasing hardness, eventually the bulk grain strength becomes greater than the strength of the interface and cracks nucleate intergranularly. Analogous to this mechanism, intergranular fatigue cracking may occur in low‐carbon martensitic steels where proeutectoid ferrite precipitates at and weakens the prior austenite grain boundaries 21 . Thus, the term ‘processing flaw’ is adopted because the formation of these flaws occurs during the final heat‐treating or manufacturing process.…”
Section: The Hall–petch–murakami Model (Hpm Model)mentioning
confidence: 99%
“…However, with increasing hardness, eventually the bulk grain strength becomes greater than the strength of the interface and cracks nucleate intergranularly. Analogous to this mechanism, intergranular fatigue cracking may occur in low‐carbon martensitic steels where proeutectoid ferrite precipitates at and weakens the prior austenite grain boundaries 21 . Thus, the term ‘processing flaw’ is adopted because the formation of these flaws occurs during the final heat‐treating or manufacturing process.…”
Section: The Hall–petch–murakami Model (Hpm Model)mentioning
confidence: 99%
“…However, in spite of the fact that the trends of the effects of k t and ρ on fatigue limit are reasonably well indicated, the physical significance of the parameter L 0 is not understood, neither is there a correlation between L 0 and any characteristic microstructural dimension. Tanaka and co‐workers [ 17, 18] have suggested that L 0 usually coincides with the length of the stage I crack, but this coincidence was not clarified. The transition from stage I (mode II) to Stage II (mode I) crack growth depends on notch geometry, stress amplitude and stress state, slip character, grain size, etc.…”
Section: The Notch Size Effect and Stress Gradientsmentioning
confidence: 99%
“…Smaller grainsized specimens, Series A, were also used, together with the series C, D, and E specimens, in order to study the role of prior austenite grain boundary. These series C, D, and E specimens were prepared to make a reduction of the deformation resistance in the narrow band of the prior austenite grain boundaries by the delayed quenching procedure [17].…”
Section: Materials and Experimental Proceduresmentioning
confidence: 99%
“…Figure 8 is a typical example of the crack path independent of the prior austenite grain boundary, which is revealed by the special etching technique [18]. Furthermore, the role of the prior austenite grain boundary was studied by using a smaller grain-sized specimen, series A, and delay-quenched specimens, series C, D, and E, whose resistance for plastic deformation at the grain boundary was intentionally weakened [17].…”
Section: Effect Of Microstructural Parameters On the Initiation And Ementioning
confidence: 99%